Policy protection for mental illness in China from the perspective of policy tools - Tan, Qingli; Cui, Hongrui; Huang, Wanyi; Peng, Jiaying; Lin, Daiheng (Frontiers in Public Health, 2025)
ObjectiveTo analyze the policies related to mental illness in China, concentrate on the deficiencies in the configuration of policy tools, and to provide reference suggestions for the government to improve the mental illness protection policies.MethodsUsing the policy tools method, we constructed a three-dimensional model of “policy tools – service providers – policy objectives,” and statistically analyzed the characteristics and reasonableness of the configuration of policy tools in each dimension and the cross-fertilization of dimensions.ResultsThe dimension of policy tools has the largest proportion of environmental tools, 46.71%. With 28 and 25.29% of supply side and demand side tools. The public health sector has the largest proportion of service-providing entities, 46.82%; and the policy objectives dimension has the largest proportion of social support, 71.35%. The policy tools used by each service subject are biased toward the environmental tools, with less application of demand side and supply side tools, and insufficient coordination of policy tools. The distribution of policy tools and objectives in existing policies is uneven, with many policy programs but little guidance, and uneven allocation of resources in policy implementation, leading to poor results.ConclusionChina should pay more attention to social support and protection, and suggests increasing the proportion of supply side and demand side tools. Public health sectors should strengthen the training of medical personnel with mental disabilities. Government will increase the investment in the construction of community medical institutions and optimize the financing model of medical insurance and the distribution of medical resources to strengthen the function of family security, and safeguard the needs of patients with mental disabilities.